2019
DOI: 10.1002/fsn3.1077
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of vacuum frying condition for producing silver carp surimi chips

Abstract: In this study, we explored the feasibility of vacuum frying to produce crisp silver carp surimi chips. The influence of three process parameters (frying temperature, frying time, and slice thickness) on the quality parameters of vacuum‐fried surimi chips (oil uptake, crispness, and optical properties) was investigated. The experimental results showed the optimal conditions were chosen as 2‐mm surimi slice being vacuum‐fried at 118°C for 2.5 min. Under these conditions, the oil content, breaking force, and colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…Hu et al . (2019) obtained similar reduced peroxide values during the VF process of surimi chips; the authors tested different processing parameters (temperature, frying time and slice thickness) and assessed the snacks' quality and oil oxidation during 100 days of storage. After extracting the oil from the samples, results showed that peroxide values increased over time and ranged from 0.04 to 0.25 g per 100 g. In both studies, the authors attributed the low peroxide values obtained after VF to the low frying temperature and the reduced interaction between oil and oxygen during the process.…”
Section: Effects Of Vacuum Fryingmentioning
confidence: 99%
“…Hu et al . (2019) obtained similar reduced peroxide values during the VF process of surimi chips; the authors tested different processing parameters (temperature, frying time and slice thickness) and assessed the snacks' quality and oil oxidation during 100 days of storage. After extracting the oil from the samples, results showed that peroxide values increased over time and ranged from 0.04 to 0.25 g per 100 g. In both studies, the authors attributed the low peroxide values obtained after VF to the low frying temperature and the reduced interaction between oil and oxygen during the process.…”
Section: Effects Of Vacuum Fryingmentioning
confidence: 99%
“…Reduction in oil uptake may be attributed to the reduced oil viscosity at elevated temperatures, which may speed up the oil drainage. The optimal conditions reported by authors include a 2-mm surimi slice, 118 C temperature, and a time of 2.5 min (Hu et al, 2019). Rapid loss of moisture during frying results in crust formation and raises the braking force of the product.…”
Section: Time and Pressurementioning
confidence: 99%
“…Pemanfaatan penggorengan vakum memberikan panas yang lebih baik dan kecepatan perpindahan massa. Metode ini dilaporkan berhasil diterapkan untuk membuat keripik buah dan mempertahankan rasa dan aroma alaminya, serta menghasilkan tekstur renyah yang baik (Hu et al, 2019). Kerenyahan merupakan atribut tekstur yang menentukan kualitas keripik.…”
Section: Teksturunclassified